A knowledge‐based system for electric motors compliance verification in a multinational‐level company. Issue 7 (14th March 2022) - Ziegler Haselein, Bruno; da Silva, Jonny Carlos
Abstract: Electric motors are highly customizable products that have to meticulously comply with the client's needs, commercial and legal requirements of each market. In this context, the configure‐to‐order (CTO) approach allows the user to define the product configuration at the time of the order and the supplier to develop a product that meets the customer's needs. This paper presents an object‐oriented knowledge‐based system (OOKBS) that integrates rule‐ and case‐based reasoning to verify the compliance of a variant‐rich and complex product—electric motors—in a multinational‐level company. The system adopts a modular structure to evaluate distinct compliance aspects, such as technical constraints and commercial requirements, and to improve the compliance assessment based on the designs of motors previously sold. The work targeted a product line with significant market share in North America, and is the result of a collaboration among the following teams: product compliance, international sales, engineering systems, and product engineering. In total, the system development involved nine experts from these areas. This study has the originality of presenting a product configuration system (PCS) that integrates rule‐based and case‐based approaches to verify the compliance of a modular product. The results indicate a reduction of 73% of internal technical queries within the prototype scope. Moreover, the system usability tests highlight the completeness of outcomes, quick access to information, and easy integration of automatic product compliance verification into the company's design flow. Furthermore, we discussed how the system was effectively implemented in a design routine based on both concurrent engineering and CTO scenarios.